Android Mobile Application Development Mobile-based Socialify Application Development as a Community Discussion Forum Provider - Novriadi Antonius Siagian; Dewi Wahyuni; Eunike Meulina Br. Tarigan (Bahasa Indonesia, 2023)
The Independent Campus is a new breakthrough from the Ministry of Education and Culture (Kemendikbud) in 2023, this program allows students to be able to gain knowledge apart from being in college, there are many activities launched in this program, one of which is Internship and Independent Study (MSIB). In the MSIB activity which was carried out from February to June 2023, the author participated in the Independent Study activity at PT Kinema Systrans Multimedia whose activities were managed by the Sub Company, namely Infinite Learning, with the title of the activity namely Mobile and Development, the activity lasted for 5 months from February 2023 to June 2023, divided into two sessions, namely the morning session and the afternoon session. Activities carried out during the Independent Study are learning soft skills that are useful in the world of work, such as professional ethics and professional self-branding. In addition, there is also mastery of hard skills such as team project management, Android application development, After the Micro Challenge is finished, it will be followed by the second stage, namely the Macro Challenge. The arrangement of groups for this stage will be determined by the mentor based on his policies. Finally, there is the Massive is invaluable because I can learn about important things in the professional world.